Comparison of Selected Elements and Processes within the Activity of European SAIs - Jan Buček (European Financial and Accounting Journal, 2022)
The study reveals that unlike SAIs from more affluent countries, the majority of SAIs from poorer countries opt to include in their audits more frequently also elements of the international comparison. The paper also brings attention to the fact that about half of the examined SAIs adopted indicators taken over from the audited entities less frequently, since the audited entities usually did not monitor or evaluate the given area. Half of the examined SAIs also provide no independent assurance that the performance indicators published by the audited entities are reliable. In addition, only a minority of the performance audits that assess the economy and effectiveness also get about to address - at least in general terms - the level of efficiency. The authorial recommendation leans towards boosting the SAIs' transparency concerning the review and publication of the implementation of their recommendations, focusing especially on the implementation side that relates to key audit recommendations. From the methodology perspective, the study makes use the questionnaire survey, the governed structured interview, content analysis of documents and comparison as the research methods.
Keywords: H83; M42; 650; SAI; Audit action; Audit report; Impact of audit activity; External audit